2020
DOI: 10.1186/s43055-020-00241-y
|View full text |Cite
|
Sign up to set email alerts
|

Flow diverter devices in the treatment of posterior communicating artery aneurysms: mid-term clinical and radiological outcomes

Abstract: Background: In the last decade, flow diverter (FD) devices are one of the widely used endovascular methods in the treatment of intracranial aneurysms. As the frequency of its use is increasing progressively, we thought that studies concerned with the use of FD at specific locations are helpful to clarify the efficacy and safety of FD as a treatment option in cerebral aneurysms. We represent our experiences in the treatment of posterior communicating artery (PCOM) aneurysms by FD devices aiming to assess its an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Twelve studies were retrospective, and of these, 7 were single center 4,5,8,15-18 and 5 multicenter. 2,6,10,19,20 Only one study had a prospective multicenter design. 3 The number of participants per study ranged from 5 to 57.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies were retrospective, and of these, 7 were single center 4,5,8,15-18 and 5 multicenter. 2,6,10,19,20 Only one study had a prospective multicenter design. 3 The number of participants per study ranged from 5 to 57.…”
Section: Resultsmentioning
confidence: 99%
“…Previously published series have postulated concerns after the implantation of FDs in these cases because of the decreased efficacy and high recurrence rates caused by the high flow through the FPComA, which prevents endothelialization, and the potential risk for ischemic complications (large infarcts) if complete arterial occlusion occurs. 4,6-10…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The term true posterior communicating artery aneurysm (PComA) is used to refer to an aneurysm arising from (PComA) and not to any other site (either the internal carotid or the posterior cerebral artery). 5 This study was conducted on 39 patients for two years who had a posterior communicating artery aneurysm that was treated surgically or endovascularly at Neurosurgery department, Al-Azhar hospitals, and Damanhur medical national institute.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, as regards the operative complications, 74.4% showed no complications, 20.5% presented with Vasospasm, 2.6% presented with Stenosis, and 2.6% presented with Intraoperative bleeding. Moubark et al, 5 reported that data talked about the complications related to the procedure that occurred in five patients (two ischemic, two TIA, and one ipsilateral distal hemorrhage).…”
Section: Discussionmentioning
confidence: 99%